Kontribusi Pekerja Wanita Terhadap Ekonomi Keluarga - Yovita Mumpuni Hartarini; Siti Khayatun; Tika Selviana (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2023)
Women's participation in the world of work has made a major contribution to family welfare. In general, women are encouraged to make a living by the demands of the household economy, this is due to the ever-increasing family needs, while real income does not always increase.. The purpose of this study was to analyze the influence of worker motivation, work pressure and income satisfaction of women cleaning swallow's nests as a family economic contribution in East Ungaran. The population in this study were 30 female swallow nest cleaning workers. The sample in this study amounted to 30 samples. This sample was obtained by using saturated sampling technique. This research data analysis tool uses multiple linear regression. The results showed that motivation (p value 0.000), work pressure (p value 0.000), and income satisfaction (p value 0.000) of female swiftlet nest cleaning workers had a positive effect on the economic contribution of families in East Ungaran. Suggestions for women's work to increase the role of women in the family economy by increasing the economic contribution through being more self-motivated at work, making work pressure a passion for work and trying to work well so as to create income satisfaction. Keep prioritizing the family, and the duties of women in the family even though they have to look for additional income.